La literatura testimonial como representación de pasados violentos en México y Colombia : "Siguiendo el corte" y "Guerra en el paraíso" (2011)
ABSTRACT: In this paper, the characteristics of the representation of violent pasts in testimonial literature are analyzed. For this purpose, it outlines the debate "about the limits of representation" which emerged from the postmodern challenge of the historiography. Keys for the integration of conflicting positions are proposed, showing how testimonial literature is a "hybrid" representation that combines reality, literary subjectivities and collective memories. As empirical evidence for these hypotheses, we present the conclusions of the analysis of "Siguiendo el corte" of Colombian sociologist Alfredo Molano and "Guerra en el paraiso" of the Mexican Writer Carlos Montemayor. Studied though the sociology of testimony, these works are seen as representations of violent past, works that do not resign to the test and the idea of the truth , as they make explicit the author's literary subjectivity and that condense memories of marginalized groups.